COMPREHENSIVE ANALYSIS OF PHYSICAL FITNESS READINESS OF CADETS (Innovate Conferences, 2025)
The comprehensive assessment of physical fitness is a key component of modern approaches to training cadets in law enforcement and military academies. This study aims to evaluate the functional readiness of cadets using a set of medico-biological tests widely applied in sports medicine, including VO₂ max, aerobic index, grip strength, and speed-strength indices.